2001
DOI: 10.1097/00005392-200111000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Early Removal of the Catheter After Laparoscopic Radical Prostatectomy

Abstract: Patients who undergo laparoscopic radical prostatectomy can have the catheter safely removed 2 to 4 days postoperatively without a higher risk of incontinence, stricture or leak related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…First, urinary extravasation seems to have no deleterious effect, as was thought previously, when extravasation was considered to increase the chances of urinary incontinence or BN sclerosis after RP. This concept arose from studies showing that ≈ 15% of patients who had RP had urinary extravasation at ≈ 4 days after surgery, and of these ≈ 11% developed BN sclerosis [17,18]. However, the present results are corroborated by Schatzl et al [14], who showed that urinary extravasation does not compromise the rate of urinary continence.…”
Section: Discussionsupporting
confidence: 73%
“…First, urinary extravasation seems to have no deleterious effect, as was thought previously, when extravasation was considered to increase the chances of urinary incontinence or BN sclerosis after RP. This concept arose from studies showing that ≈ 15% of patients who had RP had urinary extravasation at ≈ 4 days after surgery, and of these ≈ 11% developed BN sclerosis [17,18]. However, the present results are corroborated by Schatzl et al [14], who showed that urinary extravasation does not compromise the rate of urinary continence.…”
Section: Discussionsupporting
confidence: 73%
“…Laparoscopic surgeons advocate that one of the advantages of laparoscopic RRP is early catheter removal, because they can create a completely watertight running anastomosis under the magnification of the laparoscopic lens. However, acute urinary retention [19] also occurred in 10.4% of patients. The earlier the catheter is removed the less time is provided for the oedema to subside.…”
Section: Discussionmentioning
confidence: 98%
“…Proponents of laparoscopic RP cite the shorter duration of catheterization as one of the advantages resulting from better visualization of the anastomosis and more precise suturing. Nadu et al [7] reported a leak rate of 15.1% and advocated the use of cystography in the decision to remove the catheter. All of these leaks were minimal.…”
Section: Discussionmentioning
confidence: 99%